Construction of Lyapunov Functions in the Theory of Regular Linear Extensions of Dynamical Systems on a Torus - Kulik, V. L. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
Lyapunov functions are considered in the form of linear combinations of quadratic forms. We study the conditions under which the linear extensions of dynamic systems on a torus are regular.